Asesmen Kinerja dalam Pembelajaran Kalam Bahasa Arab Siswa MTs Tahun 2023: Penelitian Pustaka Melalui Google Scholar - Muslimah, Maziyyatul; Karimah, Siti Zumrotun Nisaul Mutiatul (Universitas KH. Mukhtar Syafaat, 2024)
The goal of this study is to thoroughly analyze the complexities of performance assessment in the context of Kalam learning, with a focus on the educational environment of Madrasah Tsanawiyah (MTs) students in 2023. The inquiry adopts a systematic review process that makes use of Google Scholar's extensive scholarly resource. The fundamental purpose of this work is to provide useful insights, particularly for educators, in order to facilitate informed judgments on the appropriate selection of performance assessment methodologies that effectively support the pedagogical endeavor. This project attempts to bridge the gap between theoretical conceptualizations and practical application by conducting a thorough examination of relevant literature, thereby developing a scholarly discourse informed by empirical foundations. This synthesis of multiple views aims to provide a significant contribution to the pedagogical discourse by providing compelling recommendations that might underpin teaching practices and evaluation frameworks in Kalam language acquisition. In conclusion, this study seeks to provide a scholarly framework for elucidating and demystifying performance assessment procedures within Kalam learning for MTs students. The outcome of this scholarly endeavour has the potential to improve the educational landscape by providing educators with discerning insights into prudent performance evaluation approaches, thereby promoting a dynamic and successful learning environment.